Pengaruh Pemberian Minyak Biji Kelor (Moringa seeds oil) Terhadap Kadar Trigliserida Pada Darah Tikus Putih Jantan Galur Wistar (Rattus norvegicus) - Amalia, Nurul; Norhayati; Chandra, M. Andi; Rusida, Esty Restiana (Acta Pharmaceutica Indonesia, 2024)
ABSTRACT Elevated triglyceride levels can be managed through non-pharmacological approaches, including the use of moringa seeds. These seeds are rich in fatty acids that exhibit potential in reducing hyperlipidemia. This research is designed to assess the impact of moringa seed oil on triglyceride concentrations in male Wistar strain white rats (Rattus norvegicus) administered with different doses. Utilizing a Posttest-Only Control Group Design, the experiment was conducted across five groups: K1 (positive control), K2 (negative control), K3 (3 mL moringa seed oil), K4 (6 mL moringa seed oil), and K5 (9 mL moringa seed oil). Measurements were taken after treatment. Statistical analysis revealed a significant difference in triglyceride levels between the negative control group and the groups treated with moringa seed oil (p = 0.018, p < 0.05), indicating the oil's effectiveness in reducing triglyceride levels. Furthermore, Post-Hoc LSD analysis showed a significant difference between K4 and K5, with p = 0.045 (p < 0.050). These findings suggest that moringa seed oil significantly reduces triglyceride levels, particularly at higher doses. This research determided the therapeutic potential of moringa seed oil in managing hyperlipidemia by lowering blood triglyceride levels in male Wistar rats (Rattus norvegicus).